Silicon-containing negative plate, preparation method thereof and lithium ion battery

By adopting a three-layer structure negative electrode material design, combined with capacity graphite, magnification graphite and prelithiated silicon oxygen materials, the difficulties in existing silicon-based negative electrode materials in terms of energy density, fast charging performance and cycle performance are solved, and more efficient lithium-ion battery performance is achieved.

CN119725388AActive Publication Date: 2025-03-28XIAOGAN CORNEX NEW ENERGY INNOVATION TECHNOLOGY CO LTD

Patent Information

Application Number
CN202510078566.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-03-28
Estimated Expiration
2045-01-17

AI Technical Summary

Technical Problem

While existing silicon-based anode materials take into account energy density, it is difficult to ensure fast charging and cycling performance.

Method used

The negative electrode material design is adopted with a three-layer structure, wherein the first silicon-containing layer includes capacity graphite and new porous silicon-carbon material, the second silicon-containing layer includes magnification graphite and prelithiated silicon-oxygen material, and the third graphite layer includes magnification graphite, and the negative electrode sheet is formed through double-layer coating technology and rolling.

Benefits of technology

Through the synergy of the three-layer structure, a gradient channel for lithium ion transmission is established in the longitudinal direction, improving the rate performance and fast charging cycle performance, while maintaining the energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725388A_ABST
    Figure CN119725388A_ABST
Patent Text Reader

Abstract

The invention provides a silicon-containing negative plate, a preparation method thereof and a lithium ion battery, and relates to the technical field of battery materials. The silicon-containing negative plate comprises a negative current collector and a negative material layer arranged on the surface of the current collector, wherein the negative material layer comprises a first silicon-containing layer, a second silicon-containing layer and a third graphite layer which are sequentially stacked on the surface of the negative current collector in the direction away from the current collector; wherein the first silicon-containing layer comprises capacity type graphite and a novel porous silicon-carbon material, the second silicon-containing layer comprises rate type graphite and a pre-lithiation silicon-oxygen material, and the third graphite layer comprises rate type graphite; through the synergistic effect of the three-layer structure of the first silicon-containing layer, the second silicon-containing layer and the third graphite layer, a gradient channel for lithium ion transmission is established in the longitudinal direction, and the phenomenon that active substances fall off due to large particle expansion can be effectively avoided, so that the rate capability and the fast charge cycle performance are effectively improved while the energy density is ensured. The invention also provides a preparation method of the silicon-containing negative plate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery materials and relates to a silicon-containing negative electrode sheet and a preparation method thereof and a lithium-ion battery. Background Art

[0002] Silicon-based negative electrodes have the advantages of high energy density and wide distribution of raw materials, and are considered to be promising negative electrode materials for the next generation of lithium-ion batteries. At present, there are two mainstream routes for silicon-based negative electrodes, one is the silicon-oxygen route (mainly silicon monoxide), and the other is the silicon-carbon route (mainly nano-silicon-carbon). Among them, the new porous silicon-carbon negative electrode (that is, nano-silicon vapor deposited in porous carbon materials) has obvious advantages in specific capacity, full-charge expansion rate, and cycle performance. The pre-lithiation silicon-oxygen negative electrode has certain advantages in rate performance. How to ensure the fast charging performance and cycle performance of the silicon negative electrode while taking into account the energy density is a major difficulty. Therefore, a more reasonable design of the pole piece end is required.

[0003] In view of this, the present invention is proposed. Summary of the invention

[0004] In view of the deficiencies and defects in the prior art, the present invention aims to provide a silicon-containing negative electrode sheet and a preparation method thereof, and a lithium-ion battery.

[0005] In order to achieve the above purpose, the following technical solutions are adopted:

[0006] The first object of the present invention is to provide a silicon-containing negative electrode sheet, comprising a negative electrode current collector and a negative electrode material layer arranged on the surface of the current collector;

[0007] The negative electrode material layer includes a first silicon-containing layer disposed on the surface of the negative electrode current collector, a second silicon-containing layer disposed on the surface of the first silicon-containing layer, and a third graphite layer disposed on the surface of the second silicon-containing layer;

[0008] The first silicon-containing layer comprises capacity-type graphite and a novel porous silicon-carbon material, the second silicon-containing layer comprises rate-type graphite and a pre-lithiation silicon-oxygen material, and the third graphite layer comprises rate-type graphite.

[0009] Further, based on the above technical solution of the present invention, in the first silicon-containing layer, the capacity of the capacity-type graphite is 355-360 mAh / g, and the compaction is 1.6-1.7 g / cm 3 ;

[0010] And / or, the capacity of the novel porous silicon-carbon material at 5mV-0.8V is 1600-1750mAh / g.

[0011] Further, based on the above technical solution of the present invention, the rate-type graphite capacity in the second silicon-containing layer and the third graphite layer is 345-355 mAh / g, and the compaction is 1.5-1.65 g / cm 3 ; Preferably, the rate of the rate-type graphite in the second silicon-containing layer is 1-1.5C lower than the rate of the rate-type graphite in the third graphite layer;

[0012] And / or, the capacity of the pre-lithiated silicon-oxygen material in the second silicon-containing layer at 5mV-0.8V is 1200-1350mAh / g.

[0013] Further, based on the above technical solution of the present invention, the raw materials used to form the first silicon-containing layer include capacitive graphite, a new porous silicon-carbon material, a conductive agent and a binder. Taking the total mass of the raw materials used to form the first silicon-containing layer as 100%, the mass fraction ratio of the capacitive graphite, the new porous silicon-carbon material, the conductive agent and the binder is (83.5%-88.4%): (7.6%-11.5%): (0.5%-1%): (3.5%-4%);

[0014] And / or, the raw materials used to form the second silicon-containing layer include rate-type graphite, pre-lithiation silicon-oxygen material, conductive agent and binder, and the mass fraction ratio of the rate-type graphite, pre-lithiation silicon-oxygen material, conductive agent and binder is (78.2%-88.5%): (7.5%-16.3%): (1%-1.5%): (3%-4%), taking the total mass of the raw materials used to form the second silicon-containing layer as 100%.

[0015] And / or, the raw materials used to form the third graphite layer include rate-type graphite, a conductive agent and a binder. Taking the total mass of the raw materials used to form the third graphite layer as 100%, the mass ratio of the rate-type graphite, the conductive agent and the binder is (95.5%-96.5%): (1%-1.5%): (2.5%-3%).

[0016] Further, based on the above technical solution of the present invention, the conductive agent in the first silicon-containing layer, the second silicon-containing layer and the third graphite layer includes conductive carbon black and / or carbon nanotubes;

[0017] and / or, the binder in the first silicon-containing layer, the second silicon-containing layer and the third graphite layer comprises at least one of styrene-butadiene rubber, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polyacrylic acid or lithium polyacrylate;

[0018] And / or, the mass fraction ratio of the binder in the second silicon-containing layer is less than or equal to the mass fraction ratio of the binder in the first silicon-containing layer.

[0019] Further, based on the above technical solution of the present invention, the conductive agent in the first silicon-containing layer and the second silicon-containing layer includes conductive carbon black and single-walled carbon nanotubes;

[0020] And / or, the binder in the first silicon-containing layer and the second silicon-containing layer includes styrene-butadiene rubber and lithium polyacrylate.

[0021] Further, based on the above technical solution of the present invention, the composite gram capacity of the negative electrode of the second silicon-containing layer is less than or equal to the composite gram capacity of the negative electrode of the first silicon-containing layer;

[0022] And / or, the surface density of the first silicon-containing layer accounts for 30%-60% of the surface density of the negative electrode material layer, the surface density of the second silicon-containing layer accounts for 30%-50% of the surface density of the negative electrode material layer, and the surface density of the third graphite layer accounts for 10%-20% of the surface density of the negative electrode material layer.

[0023] The second object of the present invention is to provide a method for preparing the above-mentioned silicon-containing negative electrode sheet, comprising the following steps:

[0024] (a) coating a raw material for forming a first silicon-containing layer and a raw material for forming a second silicon-containing layer on at least one side of a current collector by a double-layer coating technique, and then drying to form a first silicon-containing layer and a second silicon-containing layer, respectively, and then rolling the first silicon-containing layer and the second silicon-containing layer;

[0025] (b) coating a raw material for forming a third graphite layer on the surface of the second silicon-containing layer, and then drying to form the third graphite layer, and then rolling the entire electrode sheet to obtain a silicon-containing negative electrode sheet.

[0026] Further, based on the above technical solution of the present invention, in step (a), the rolling includes a first rolling and a second rolling, and the first rolling compaction is 1.3-1.4 g / cm 3 The second roller compaction is 1.6-1.65g / cm 3 ;

[0027] And / or, in step (b), the roller compaction is 1.55-1.6 g / cm 3 .

[0028] The third object of the present invention is to provide a lithium ion battery, comprising the silicon-containing negative electrode sheet provided by the first object of the present invention and the silicon-containing negative electrode sheet prepared by the preparation method provided by the second object of the present invention.

[0029] Compared with the prior art, the technical solution of the present invention has at least the following technical effects:

[0030] (1) The present invention provides a silicon-containing negative electrode sheet, comprising a negative electrode current collector and a negative electrode material layer arranged on the surface of the current collector, the negative electrode material layer comprising a first silicon-containing layer, a second silicon-containing layer and a third graphite layer which are sequentially stacked on the surface of the negative electrode current collector in a direction away from the current collector; wherein the first silicon-containing layer comprises capacity-type graphite and a new porous silicon-carbon material, the second silicon-containing layer comprises rate-type graphite and a pre-lithiation silicon-oxygen material, and the third graphite layer comprises rate-type graphite; through the synergistic effect of the three-layer structure of the first silicon-containing layer, the second silicon-containing layer and the third graphite layer, a gradient channel (fast-buffer-slow) for lithium ion transmission is established in the longitudinal direction, and the phenomenon of active material shedding caused by large particle expansion can be effectively avoided, thereby effectively improving the rate performance and fast charging cycle performance while ensuring the energy density.

[0031] (2) The present invention provides a method for preparing the above-mentioned silicon-containing negative electrode sheet, which is simple to operate and saves time and baking costs compared to the conventional three-layer structure in which each layer of the negative electrode material layer is coated with a single layer. Moreover, the entire coating process can be achieved on the basis of existing equipment without increasing equipment costs.

[0032] (3) The present invention provides a lithium-ion battery comprising the above silicon-containing negative electrode sheet. In view of the advantages of the silicon-containing negative electrode sheet, the lithium-ion battery made therefrom has good energy density, good rate performance and fast charge cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a schematic diagram of the structure of the silicon-containing negative electrode sheet of the present invention;

[0034] In the figure, 1-current collector; 2-first silicon-containing layer; 3-second silicon-containing layer; 4-third graphite layer. DETAILED DESCRIPTION

[0035] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.

[0036] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.

[0037] According to a first aspect of the present invention, there is provided a silicon-containing negative electrode sheet, the structural schematic diagram of which is as follows: Figure 1 As shown, the silicon-containing negative electrode sheet specifically includes a negative electrode current collector 1 and a negative electrode material layer arranged on the surface of the current collector;

[0038] The negative electrode material layer includes a first silicon-containing layer 2 disposed on the surface of the negative electrode current collector, a second silicon-containing layer 3 disposed on the surface of the first silicon-containing layer, and a third graphite layer 4 disposed on the surface of the second silicon-containing layer;

[0039] The first silicon-containing layer 2 comprises capacity-type graphite and a novel porous silicon-carbon material, the second silicon-containing layer 3 comprises rate-type graphite and a pre-lithiated silicon-oxygen material, and the third graphite layer 4 comprises rate-type graphite.

[0040] According to the characteristics of the material itself, the present invention makes a more reasonable design for the pole piece end: the graphite layer (i.e., the third graphite layer) is set as the outermost layer, and the characteristic of fast lithium ion diffusion of rate-type graphite is utilized to effectively improve the rate performance of the overall pole piece and avoid lithium precipitation on the surface of the negative electrode; the silicon oxide layer (i.e., the second silicon-containing layer) is set as the middle layer, mainly utilizing the characteristic that the silicon oxide negative electrode has better rate performance than the silicon carbon negative electrode, providing a buffer layer for slowing down the diffusion rate of lithium ions, and considering that the silicon oxide negative electrode expands more, placing it in the middle layer can provide an effective buffer space for particle expansion in the longitudinal thickness direction, thereby reducing the expansion of the pole piece itself; the silicon carbon layer (i.e., the first silicon-containing layer) is set as the inner layer, mainly considering the characteristics of high silicon carbon capacity and small expansion, while ensuring the energy density of the battery cell, avoiding the shedding of active substances caused by large particle expansion, thereby ensuring the cycle life. Through the synergistic effect of the first silicon-containing layer, the second silicon-containing layer and the third graphite layer, a gradient channel (fast-buffer-slow) for lithium ion transmission is established in the vertical direction, and the shedding of active substances caused by large particle expansion can be effectively avoided, thereby effectively improving the rate performance and fast charging cycle performance while ensuring the energy density.

[0041] Compared with the traditional improvement of the negative electrode material itself (such as coating, doping or modification, etc.), the present invention is designed at the electrode end according to the material characteristics. The raw materials used are simple and easy to obtain, and no additional processing is required. It has obvious cost advantages and provides more feasibility in industrialization.

[0042] As an optional embodiment of the technical solution of the present invention, the capacity of the capacity-type graphite in the first silicon-containing layer is 355-360 mAh / g (for example, 355 mAh / g, 356 mAh / g, 358 mAh / g or 360 mAh / g, etc.), and the compaction is 1.6-1.7 g / cm 3 (For example, 1.6 g / cm 3 , 1.62g / cm 3 , 1.64g / cm 3 , 1.65g / cm 3 、1.66g / cm 3 、1.68g / cm 3 , 1.7g / cm 3 wait);

[0043] And / or, the source of the novel porous silicon-carbon material in the first silicon-containing layer (i.e., nano-silicon vapor-deposited in the porous carbon material) is not limited, and can be prepared by itself according to the existing technology, or can be purchased commercially. Its capacity is further limited, and the capacity of the novel porous silicon-carbon material at 5mV-0.8V is 1600-1750mAh / g (for example, 1600mAh / g, 1620mAh / g, 1650mAh / g, 1660mAh / g, 1680mAh / g, 1700mAh / g, 1720mAh / g, 1740mAh / g or 1750mAh / g, etc.). There is no specific limitation on the preparation method of the novel porous silicon-carbon material, as long as the capacity meets the requirements.

[0044] The energy density of the battery cell is ensured by further limiting the capacity of the capacitive graphite and the new porous silicon-carbon material in the first silicon-containing layer.

[0045] As an optional embodiment of the technical solution of the present invention, the rate-type graphite capacity in the second silicon-containing layer and the third graphite layer is 345-355 mAh / g (for example, 345 mAh / g, 346 mAh / g, 348 mAh / g, 350 mAh / g, 352 mAh / g, 354 mAh / g or 355 mAh / g, etc.), and the compaction is 1.5-1.65 g / cm 3 (For example, 1.5 g / cm 3 , 1.52g / cm 3 , 1.54g / cm 3 , 1.56g / cm 3 , 1.58g / cm 3 , 1.6g / cm 3 , 1.62g / cm 3 , 1.64g / cm 3 or 1.65g / cm 3 wait);

[0046] Preferably, the rate of the rate-type graphite in the second silicon-containing layer is 1-1.5C lower than that of the rate-type graphite in the third graphite layer; in this way, while ensuring the construction of a gradient channel (fast-buffered) for lithium ion transmission, it is also beneficial to reduce material costs (the higher the rate of the rate-type graphite, the more expensive it is).

[0047] As an optional implementation of the technical solution of the present invention, the capacity of the pre-lithiated silicon oxygen material in the second silicon-containing layer at 5mV-0.8V is 1200-1350mAh / g (for example, 1200mAh / g, 1220mAh / g, 1250mAh / g, 1260mAh / g, 1280mAh / g, 1300mAh / g, 1320mAh / g, 1340mAh / g or 1350mAh / g, etc.). There is no specific limitation on the preparation method of the pre-lithiated silicon oxygen material, as long as the capacity meets the requirements.

[0048] As an optional implementation mode of the technical solution of the present invention, the raw materials for forming the first silicon-containing layer include capacity-type graphite, a new porous silicon-carbon material, a conductive agent and a binder. Taking the total mass of the above raw materials as 100%, the mass fraction of the capacity-type graphite is 83.5%-88.4% (for example, 83.5%, 84%, 85%, 86%, 87% or 88%, etc.), the mass fraction of the new porous silicon-carbon material is 7.6%-11.5% (for example, 7.6%, 8%, 8.5%, 9%, 9.5%, 10%, 11% or 11.5%, etc.), the mass fraction of the conductive agent is 0.5%-1% (for example, 0.6%, 0.7%, 0.8% or 1.0%, etc.), and the mass fraction of the binder is 3.5%-4% (for example, 3.6%, 3.7%, 3.8% or 4.0%, etc.). That is, the mass fraction ratio of the capacity-type graphite, the new porous silicon-carbon material, the conductive agent and the binder is (83.5%-88.4%): (7.6%-11.5%): (0.5%-1%): (3.5%-4%).

[0049] As an optional implementation scheme of the technical solution of the present invention, the raw materials for forming the second silicon-containing layer include rate-type graphite, pre-lithiation silicon-oxygen material, conductive agent and binder. Taking the total mass of the above raw materials as 100%, the mass fraction of the rate-type graphite is 78.2%-88.5% (for example, 78.2%, 80%, 82%, 84%, 85%, 86%, 87% or 88%, etc.), and the mass fraction of the pre-lithiation silicon-oxygen material is 7.5%-16.3% (for example, 7.5%, 8%, 9%, 10%, 12%, 14%, 15%, 16% or 16.3%, etc.), the mass fraction of the conductive agent is 1%-1.5% (for example, 1%, 1.2%, 1.4% or 1.5%, etc.), the mass fraction of the binder is 3%-4% (for example, 3.0%, 3.2%, 3.5%, 3.6%, 3.7%, 3.8% or 4.0%, etc.), that is, the mass fraction ratio of the rate-type graphite, the pre-lithiation silicon oxide material, the conductive agent and the binder is (78.2%-88.5%): (7.5%-16.3%): (1%-1.5%): (3%-4%).

[0050] As an optional implementation of the technical solution of the present invention, the raw materials used to form the third graphite layer include rate-type graphite, a conductive agent and a binder. Taking the total mass of the above raw materials as 100%, the mass fraction of the rate-type graphite is 95.5%-96.5% (for example, 95.5%, 95.8%, 96.0%, 96.2%, 96.4% or 96.5%), the mass fraction of the conductive agent is 1%-1.5% (for example, 1%, 1.2%, 1.4% or 1.5%), and the mass fraction of the binder is 2.5%-3% (for example, 2.6%, 2.7%, 2.8% or 3.0%). That is, the mass fraction ratio of the rate-type graphite, the conductive agent and the binder is (95.5%-96.5%): (1%-1.5%): (2.5%-3%).

[0051] As an optional implementation of the technical solution of the present invention, the conductive agent in the first silicon-containing layer, the second silicon-containing layer and the third graphite layer includes conductive carbon black and / or carbon nanotubes; wherein the carbon nanotubes include single-walled and / or multi-walled carbon nanotubes. Preferably, the conductive agent in the first silicon-containing layer and the second silicon-containing layer includes conductive carbon black and single-walled carbon nanotubes; further preferably, the mass ratio of the conductive agent in the second silicon-containing layer is greater than or equal to the mass ratio of the conductive agent in the first silicon-containing layer.

[0052] As an optional implementation of the technical solution of the present invention, the binder in the first silicon-containing layer, the second silicon-containing layer and the third graphite layer includes at least one of styrene-butadiene rubber (SBR), sodium carboxymethyl cellulose (CMC-Na), lithium carboxymethyl cellulose (CMC-Li), polyacrylic acid (PAA) or lithium polyacrylate (PAA-Li).

[0053] Preferably, the binder in the first silicon-containing layer and the second silicon-containing layer includes styrene-butadiene rubber and lithium polyacrylate; further preferably, the binder mass fraction ratio in the second silicon-containing layer is less than or equal to the binder mass fraction ratio in the first silicon-containing layer.

[0054] By further limiting the specific types and relative mass ratios of the binders in the first silicon-containing layer and the second silicon-containing layer, the expansion of the first silicon-containing layer and the second silicon-containing layer can be effectively suppressed and the conductivity of the second silicon-containing layer can be ensured (styrene-butadiene rubber and lithium polyacrylate have a good inhibitory effect on the expansion of the electrode, but the more the total amount of binder, the worse the conductivity).

[0055] As an optional implementation of the technical solution of the present invention, the composite gram capacity of the second silicon-containing layer negative electrode is less than or equal to the composite gram capacity of the first silicon-containing layer negative electrode.

[0056] The calculation formula for the composite gram capacity of the first silicon-containing layer negative electrode is: composite gram capacity = (graphite capacity × graphite mass ratio + silicon-carbon capacity × silicon-carbon mass ratio) / (graphite mass ratio + silicon-carbon mass ratio).

[0057] The calculation formula for the composite gram capacity of the second silicon-containing layer negative electrode is: composite gram capacity = (graphite capacity × graphite mass ratio + silicon oxygen capacity × silicon oxygen mass ratio) / (graphite mass ratio + silicon oxygen mass ratio).

[0058] As an optional implementation scheme of the technical solution of the present invention, the surface density of the first silicon-containing layer accounts for 30%-60% (for example, 30%, 35%, 40%, 45%, 50%, 55% or 60%) of the surface density of the negative electrode material layer (i.e., the first silicon-containing layer + the second silicon-containing layer + the third graphite layer) of the entire electrode (excluding the current collector), the surface density of the second silicon-containing layer accounts for 30%-50% (for example, 30%, 35%, 40%, 45% or 50%) of the surface density of the negative electrode material layer, and the surface density of the third graphite layer accounts for 10%-20% (for example, 10%, 12%, 15%, 18% or 20%) of the surface density of the negative electrode material layer.

[0059] According to a second aspect of the present invention, there is also provided a method for preparing the above-mentioned silicon-containing negative electrode sheet, comprising the following steps:

[0060] (a) coating a raw material for forming a first silicon-containing layer and a raw material for forming a second silicon-containing layer on at least one side of a current collector by a double-layer coating technique, and then drying to form a first silicon-containing layer and a second silicon-containing layer, respectively, and then rolling the first silicon-containing layer and the second silicon-containing layer;

[0061] (b) coating a raw material for forming a third graphite layer on the surface of the second silicon-containing layer, and then drying to form the third graphite layer, and then rolling the entire electrode sheet to obtain a silicon-containing negative electrode sheet.

[0062] This preparation method can be realized on the basis of existing equipment (currently dual-die coating machines are more common, and triple-die coating machines need to be customized separately), without increasing equipment costs, and the slurry properties (viscosity and solid content) of the first silicon-containing layer and the second silicon-containing layer are similar. Double-layer coating is easier to operate (no interface problems such as pinholes will occur) and saves costs (saving time costs and baking costs compared to single-layer coating).

[0063] As an optional implementation of the technical solution of the present invention, in step (a), the rolling includes a first rolling and a second rolling, and the first rolling compaction is 1.3-1.4g / cm 3 (e.g. 1.32 g / cm 3 , 1.35g / cm 3 , 1.38g / cm 3 or 1.4 g / cm 3 The second roller compaction is 1.6-1.65g / cm 3 (e.g. 1.60 g / cm 3 , 1.62g / cm 3 or 1.65g / cm 3 The secondary rolling method can effectively improve the full-charge expansion and rate performance of the silicon negative electrode.

[0064] As an optional implementation of the technical solution of the present invention, in step (b), the roller compaction is 1.55-1.6 g / cm 3 (e.g. 1.55 g / cm 3 , 1.58g / cm 3 or 1.60g / cm 3 wait).

[0065] According to a third aspect of the present invention, there is also provided a lithium-ion battery, comprising the above-mentioned silicon-containing negative electrode sheet and the silicon-containing negative electrode sheet prepared by the above-mentioned preparation method.

[0066] In view of the advantages of the silicon-containing negative electrode sheet provided by the present invention, the lithium-ion battery prepared therefrom has good energy density as well as good rate performance and fast charging cycle performance.

[0067] The present invention will be further described in detail below with reference to specific embodiments and comparative examples.

[0068] Example 1

[0069] This embodiment provides a silicon-containing negative electrode sheet, comprising a negative electrode current collector (carbon-coated copper foil) and a negative electrode material layer disposed on the surface of the current collector;

[0070] The negative electrode material layer includes a first silicon-containing layer (first coating layer) disposed on the surface of the negative electrode current collector, a second silicon-containing layer (second coating layer) disposed on the surface of the first silicon-containing layer, and a third graphite layer (third coating layer) disposed on the surface of the second silicon-containing layer;

[0071] The first silicon-containing layer comprises a capacity-type graphite (capacity of 355 mAh / g, compaction of 1.6 g / cm 3 ) and a new porous silicon-carbon material (purchased from the market, with a capacity of 1620mAh / g at 5mV-0.8V); the first silicon-containing layer negative electrode composite capacity is 500mAh / g; in the first silicon-containing layer, the mass fractions of capacity-type graphite, new porous silicon-carbon material, conductive agent and binder are 83.6%, 11.4%, 1% and 4% respectively;

[0072] The second silicon-containing layer contains rate-type graphite 1 (rate 2.5C, capacity 350 mAh / g, compaction 1.6 g / cm 3 ) and pre-lithiation silicon-oxygen material (purchased from the market, with a capacity of 1250mAh / g at 5mV-0.8V); the second silicon-containing layer negative electrode composite capacity is 460mAh / g. In the second silicon-containing layer, the mass fractions of rate-type graphite 1, pre-lithiation silicon-oxygen material, conductive agent and binder are 83.3%, 11.7%, 1.5% and 3.5% respectively;

[0073] The third graphite layer contains rate-type graphite 2 (rate 4C, capacity 350 mAh / g, compaction 1.55 g / cm 3 ); In the third graphite layer, the mass fractions of the rate-type graphite 2, the conductive agent and the binder are 95.9%, 1.3% and 2.8%, respectively.

[0074] The method for preparing the silicon-containing negative electrode sheet of this embodiment comprises the following steps:

[0075] (1) mixing the capacity type graphite, the novel porous silicon-carbon material, the conductive carbon black, the single-walled carbon nanotube, the SBR, and the PAA-Li with deionized water in a mass ratio of 83.6%:11.4%:0.9%:0.1%:1%:3% of the first silicon-containing layer to form a slurry 1;

[0076] The rate-type graphite 1, the pre-lithiation silicon-oxygen material, the conductive carbon black, the single-walled carbon nanotube, the SBR, the PAA-Li and the deionized water are mixed uniformly according to the mass ratio of the second silicon-containing layer composition of 83.3%:11.7%:1.4%:0.1%:1%:2.5% to form a slurry 2;

[0077] Slurry 1 and slurry 2 were coated on the current collector using a double-layer coating technique, and the surface density of the first silicon-containing layer was controlled to be 40% of the surface density of the entire pole piece (excluding the current collector), and the surface density of the second silicon-containing layer was controlled to be 40% of the surface density of the entire pole piece (excluding the current collector). After drying, a second roll pressing was performed, and the first roll pressing compaction was 1.3 g / cm 3 The second roller compaction is 1.6g / cm 3 .

[0078] (2) The rate-type graphite 2, conductive carbon black, CMC-Na, and SBR were mixed evenly with deionized water in a mass ratio of 95.9%:1.3%:1.3%:1.5% for the third graphite layer composition to form slurry 3, and the slurry 3 was applied to the surface of the second silicon-containing layer, and the surface density of the third graphite layer was controlled to be 20% of the surface density of the entire electrode (excluding the current collector). After drying, the slurry was rolled and the rolling compaction was controlled to be 1.55 g / cm 3 , and obtain a silicon-containing negative electrode sheet.

[0079] Example 2

[0080] The present embodiment provides a silicon-containing negative electrode sheet and a method for preparing the same. The present embodiment is basically the same as Embodiment 1, except that in steps (1) and (2), the surface density of the first silicon-containing layer, the second silicon-containing layer and the third graphite layer respectively accounts for 50%, 30% and 20% of the entire electrode sheet (excluding the current collector).

[0081] Example 3

[0082] The present embodiment provides a silicon-containing negative electrode sheet and a method for preparing the same. The present embodiment is basically the same as Embodiment 1, except that in steps (1) and (2), the surface density of the first silicon-containing layer, the second silicon-containing layer and the third graphite layer respectively accounts for 60%, 20% and 20% of the surface density of the entire electrode sheet (excluding the current collector).

[0083] Comparative Example 1

[0084] This comparative example provides a silicon-containing negative electrode sheet. Compared with Example 1, except that the second silicon-containing layer is not arranged between the first silicon-containing layer and the third graphite layer, and the surface density of the first silicon-containing layer is 80% of the surface density of the entire electrode sheet (excluding the current collector), and the surface density of the third graphite layer is 20% of the surface density of the entire electrode sheet (excluding the current collector), the rest of the structural composition is the same as Example 1.

[0085] The method for preparing the silicon-containing negative electrode sheet of this comparative example comprises the following steps:

[0086] (1) mixing the capacity type graphite, the novel porous silicon-carbon material, the conductive carbon black, the single-walled carbon nanotube, the SBR, and the PAA-Li with deionized water in a mass ratio of 83.6%:11.4%:0.9%:0.1%:1%:3% of the first silicon-containing layer to form a slurry 1;

[0087] Slurry 1 was coated on the current collector, and its surface density was controlled to be 80% of the entire electrode (excluding the current collector). After drying, it was rolled twice. The first rolling compaction was 1.3 g / cm 3 The second roller compaction is 1.6g / cm 3 , obtaining a first silicon-containing layer;

[0088] (2) mixing the rate type graphite 2, conductive carbon black, CMC-Na, SBR and deionized water in a mass ratio of 95.9%:1.3%:1.3%:1.5% of the third graphite layer composition to form a slurry 3;

[0089] Slurry 3 was applied to the surface of the first silicon-containing layer, and the surface density of the third graphite layer was controlled to be 20% of the surface density of the entire electrode (excluding the current collector). After drying, the slurry was rolled and the compaction was controlled to be 1.55 g / cm 3 , and obtain a silicon-containing negative electrode sheet.

[0090] Comparative Example 2

[0091] This comparative example provides a silicon-containing negative electrode sheet, comprising a negative electrode current collector and a negative electrode material layer disposed on the surface of the current collector;

[0092] The negative electrode material layer includes a first silicon-containing layer disposed on the surface of the negative electrode current collector and a third graphite layer disposed on the surface of the first silicon-containing layer;

[0093] The first silicon-containing layer comprises a capacity-type graphite (capacity of 355 mAh / g, compaction of 1.6 g / cm 3 ) and pre-lithiated silicon oxide material (the capacity at 5mV-0.8V is 1250mAh / g), the composite capacity of the negative electrode of the first silicon-containing layer is 460mAh / g; in the first silicon-containing layer, the mass fractions of capacity-type graphite, pre-lithiated silicon oxide material, conductive agent and binder are 83.8%, 11.2%, 1.5% and 3.5% respectively.

[0094] The third graphite layer contains rate-type graphite 2 (rate 4C, 350 mAh / g, compacted to 1.55 g / cm 3 ); In the third graphite layer, the mass fractions of the rate-type graphite 2, the conductive agent and the binder are 95.9%, 1.3% and 2.8%, respectively.

[0095] The method for preparing the silicon-containing negative electrode sheet of this comparative example comprises the following steps:

[0096] (1) Capacitive graphite, pre-lithiation silicon-oxygen material, conductive carbon black, single-walled carbon nanotubes, SBR, and PAA-Li were mixed with deionized water in a mass ratio of the first silicon-containing layer: 83.8%: 11.2%: 1.4%: 0.1%: 1%: 2.5% to form a slurry, and then the slurry was coated on the current collector to control its surface density to 80% of the entire electrode (excluding the current collector). After drying, a second rolling press was performed, and the first rolling press compaction was 1.3 g / cm 3 The second roller compaction is 1.6g / cm 3 obtaining a first silicon-containing layer;

[0097] (2) The rate-type graphite 2, conductive carbon black, CMC-Na, and SBR were mixed evenly with deionized water in a mass ratio of the third graphite layer: 95.9%: 1.3%: 1.3%: 1.5% to form a slurry, which was applied to the surface of the first silicon-containing layer. The surface density of the third graphite layer was controlled to be 20% of the entire electrode (excluding the current collector). After drying, the surface density was controlled to be 1.55 g / cm 3 , and obtain a silicon-containing negative electrode sheet.

[0098] Comparative Example 3

[0099] This comparative example provides a silicon-containing negative electrode sheet, comprising a negative electrode current collector and a negative electrode material layer disposed on the surface of the current collector;

[0100] The negative electrode material layer includes a first silicon-containing layer disposed on the surface of the negative electrode current collector and a third graphite layer disposed on the surface of the first silicon-containing layer;

[0101] The first silicon-containing layer comprises a capacity-type graphite (capacity of 355 mAh / g, compaction of 1.6 g / cm 3 ) and pre-lithiated silicon oxide material (the capacity at 5mV-0.8V is 1250mAh / g), the composite capacity of the negative electrode of the first silicon-containing layer is 500mAh / g; in the first silicon-containing layer, the mass fractions of capacity-type graphite, pre-lithiated silicon oxide material, conductive agent and binder are 79.6%, 15.4%, 1% and 4% respectively.

[0102] The third graphite layer contains rate-type graphite 2 (rate 4C, 350 mAh / g, compacted to 1.55 g / cm 3 ); In the third graphite layer, the mass fractions of the rate-type graphite 2, the conductive agent and the binder are 95.9%, 1.3% and 2.8%, respectively.

[0103] The method for preparing the silicon-containing negative electrode sheet of this comparative example comprises the following steps:

[0104] (1) Capacitive graphite, pre-lithiation silicon-oxygen material, conductive carbon black, single-walled carbon nanotubes, SBR, and PAA-Li are mixed evenly with deionized water according to the mass ratio of 79.6%: 15.4%: 0.9%: 0.1%: 1%: 3% of the first silicon-containing layer composition (this mass ratio is calculated based on the same compound gram volume, and the ratio of graphite to silicon-oxygen is different from that in Comparative Example 1 due to the smaller silicon-oxygen capacity, and the ratios of the other components are the same) to form a slurry, and then the slurry is coated on the current collector, and its surface density is controlled to be 80% of the entire electrode (excluding the current collector). After drying, a second rolling is performed, and the first rolling compaction is 1.3 g / cm 3 The second roller compaction is 1.6g / cm 3 , obtaining a first silicon-containing layer;

[0105] (2) The rate-type graphite 2, conductive carbon black, CMC-Na, and SBR were mixed evenly with deionized water in a mass ratio of 95.9%:1.3%:1.3%:1.5% in the composition of the third graphite layer to form a slurry, which was then coated on the surface of the first silicon-containing layer. The surface density of the third graphite layer was controlled to be 20% of the entire electrode (excluding the current collector). After drying, the slurry was rolled and the rolling compaction was controlled to be 1.55 g / cm 3 , and obtain a silicon-containing negative electrode sheet.

[0106] Comparative Example 4

[0107] This comparative example provides a silicon-containing negative electrode sheet, comprising a negative electrode current collector and a negative electrode material layer disposed on the surface of the current collector;

[0108] The negative electrode material layer includes a rate-type graphite 2 (rate 4C, 350 mAh / g, compacted to 1.55 g / cm 3 ) and new porous silicon-carbon material (the capacity at 5mV-0.8V is 1620mAh / g), and the composite capacity is 460mAh / g; in the negative electrode material layer, the mass fractions of rate-type graphite 2, new porous silicon-carbon material, conductive agent and binder are 86.7%, 8.3%, 1.5% and 3.5% respectively.

[0109] The method for preparing the silicon-containing negative electrode sheet of this comparative example comprises the following steps:

[0110] The rate-type graphite 2, the new porous silicon-carbon material, the conductive carbon black, the single-walled carbon nanotubes, the SBR, and the PAA-Li were mixed evenly with deionized water in a mass ratio of 86.7%: 8.3%: 1.4%: 0.1%: 1%: 2.5% to form a slurry, which was then coated on the current collector and rolled for a second time after drying. The first rolling compaction was 1.3 g / cm 3 The second roller compaction is 1.55g / cm 3 , and obtain a silicon-containing negative electrode sheet.

[0111] Comparative Example 5

[0112] This comparative example provides a silicon-containing negative electrode sheet, comprising a negative electrode current collector and a negative electrode material layer disposed on the surface of the current collector;

[0113] The negative electrode material layer includes a rate-type graphite 2 (rate 4C, 350 mAh / g, compacted to 1.55 g / cm 3 ) and pre-lithiated silicon oxide material (the capacity at 5mV-0.8V is 1250mAh / g), and the composite capacity is 460mAh / g; in the negative electrode material layer, the mass fractions of rate-type graphite 2, pre-lithiated silicon oxide material, conductive agent and binder are 83.3%, 11.7%, 1.5% and 3.5% respectively.

[0114] The method for preparing the silicon-containing negative electrode sheet of this comparative example comprises the following steps:

[0115] The rate-type graphite 2, pre-lithiation silicon-oxygen material, conductive carbon black, single-walled carbon nanotubes, SBR, and PAA-Li were mixed with deionized water in a mass ratio of 83.3%: 11.7%: 1.4%: 0.1%: 1%: 2.5% to form a slurry, and then the slurry was coated on the current collector and rolled for a second time after drying. The first rolling compaction was 1.3 g / cm 3 The second roller compaction is 1.55g / cm 3 , and obtain a silicon-containing negative electrode sheet.

[0116] Comparative Example 6

[0117] This comparative example provides a silicon-containing negative electrode sheet, comprising a negative electrode current collector and a negative electrode material layer disposed on the surface of the current collector;

[0118] The negative electrode material layer includes a rate-type graphite 2 (rate 4C, 350 mAh / g, compacted to 1.55 g / cm 3 ); In the negative electrode material layer, the mass fractions of rate-type graphite 2, conductive agent and binder are 95.9%, 1.3% and 2.8% respectively.

[0119] The method for preparing the silicon-containing negative electrode sheet of this comparative example comprises the following steps:

[0120] The rate-type graphite 2, conductive carbon black, CMC-Na, and SBR were mixed with deionized water in a mass ratio of 95.9%:1.3%:1.3%:1.5% to form a slurry, and then the slurry was coated on the current collector, and the roller was pressed after drying to control the roller compaction to 1.55g / cm 3 , and obtain the negative electrode sheet.

[0121] Comparative Example 7

[0122] This comparative example provides a silicon-containing negative electrode sheet, comprising a negative electrode current collector and a negative electrode material layer disposed on the surface of the current collector;

[0123] The negative electrode material layer includes a first silicon-containing layer disposed on the surface of the negative electrode current collector, a second silicon-containing layer disposed on the surface of the first silicon-containing layer, and a third graphite layer disposed on the surface of the second silicon-containing layer;

[0124] The first silicon-containing layer comprises a capacity-type graphite (capacity of 355 mAh / g, compaction of 1.6 g / cm 3 ) and pre-lithiated silicon-oxygen material (5mV-0.8V capacity is 1250mAh / g), the composite capacity is 460mAh / g; in the first silicon-containing layer, the mass fractions of capacity-type graphite, pre-lithiated silicon-oxygen material, conductive agent and binder are 84.3%, 11.2%, 1% and 3.5% respectively;

[0125] The second silicon-containing layer contains rate-type graphite 1 (rate 2.5C, 350 mAh / g, compaction 1.6 g / cm 3 ) and a new porous silicon-carbon material (5mV-0.8V capacity is 1620mAh / g), and the composite capacity is 500mAh / g; in the second silicon-containing layer, the mass fractions of rate-type graphite 1, new porous silicon-carbon, conductive agent and binder are 83.2%, 11.3%, 1.5% and 4% respectively;

[0126] The third graphite layer contains rate-type graphite 2 (rate 4C, 350 mAh / g, compacted to 1.55 g / cm 3 ); In the third graphite layer, the mass fractions of rate-type graphite 2, conductive agent and binder are 95.9%, 1.3% and 2.8%, respectively.

[0127] The method for preparing the silicon-containing negative electrode sheet of this comparative example comprises the following steps:

[0128] (1) mixing the capacity type graphite, the pre-lithiation silicon-oxygen material, the conductive carbon black, the single-walled carbon nanotube, the SBR, and the PAA-Li with deionized water in a mass ratio of 84.3%:11.2%:0.9%:0.1%:1%:2.5% of the first silicon-containing layer composition to form a slurry 1;

[0129] The rate-type graphite 1, the novel porous silicon carbon, the conductive carbon black, the single-walled carbon nanotube, the SBR, the PAA-Li and the deionized water are mixed uniformly in a mass ratio of the second silicon-containing layer: 83.2%: 11.3%: 1.4%: 0.1%: 1%: 3% to form a slurry 2;

[0130] Slurry 1 and slurry 2 were coated on the current collector using a double-layer coating technique, and the surface density of the first silicon-containing layer was controlled to be 40% of the entire pole piece (excluding the current collector), and the surface density of the second silicon-containing layer was controlled to be 40% of the entire pole piece (excluding the current collector). After drying, a second roll pressing was performed, and the first roll pressing compaction was 1.3 g / cm 3The second roller compaction is 1.6g / cm 3 .

[0131] (2) The rate-type graphite 2, carbon black, CMC-Na, and SBR were mixed evenly with deionized water in a mass ratio of the third graphite layer: 95.9%: 1.3%: 1.3%: 1.5% to form a slurry 3, and the slurry 3 was applied to the surface of the second silicon-containing layer, and the surface density of the third graphite layer was controlled to be 20% of the entire electrode (excluding the current collector). After drying, the slurry was rolled and the rolling compaction was controlled to be 1.55 g / cm 3 , and obtain a silicon-containing negative electrode sheet.

[0132] The electrode compositions of Examples 1 to 3 and Comparative Examples 1 to 7 are briefly summarized as shown in Table 1.

[0133] Table 1

[0134]

[0135]

[0136] In order to compare the technical effects of the embodiments and comparative examples, the following experimental examples are specially set up.

[0137] The specific method for manufacturing the lithium-ion battery obtained by assembling the silicon-containing negative electrode sheets obtained in Examples 1 to 3 and Comparative Examples 1 to 7 is as follows:

[0138] Positive electrode sheet: NCM-9 as positive electrode active material, conductive carbon black as conductive agent, PVDF as binder are mixed with NMP in a mass ratio of 96.7%:2%:1.3% to obtain positive electrode slurry; the positive electrode slurry is coated on the surface of positive electrode current collector aluminum foil, dried, rolled and cut to obtain positive electrode sheet, and the positive electrode compaction is 3.45g / cm 3 , the positive electrode surface density is 300-400g / m 2 (The surface density is designed based on an N / P ratio of 1.12, where the N / P ratio is the ratio of the negative electrode capacity to the positive electrode capacity under the same area. The surface density of the negative electrode of the present invention is the same, so the surface density of the positive electrode needs to be calculated through the NP ratio).

[0139] Negative electrode sheet: The negative electrode sheet obtained in the embodiment and the comparative example is cut to obtain a cut negative electrode sheet.

[0140] The above-mentioned positive electrode sheet, negative electrode sheet and separator (purchased) are stacked to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, an electrolyte (1M LiPF6, DMC:EMC:FEC:EC=40:40:15:5) is injected, and a lithium-ion battery is obtained through vacuum packaging, standing, formation, aging, capacity division and other processes.

[0141] Then, the electrical performance of the lithium-ion batteries prepared in the embodiments and comparative examples was tested, and the test results are shown in Table 2.

[0142] Among them, the negative electrode surface density is weighed by analytical balance 10cm 2 The mass of the disc is obtained, and the negative electrode surface density (g / m 2 ) = 10cm of negative electrode sheet (including foil) 2 Disk mass value (mg / 10cm 2 )-10cm of foil 2 Disk mass value (mg / 10cm 2 );

[0143] Energy density (Wh / kg) = discharge energy obtained by battery capacity division (Wh) / battery weight (kg);

[0144] Method for detecting the full-charge expansion rate of the negative electrode sheet: Use a micrometer to measure the thickness of the negative electrode sheet after rolling and in the fully-charged state, and calculate the full-charge expansion rate by the formula: Full-charge expansion rate = (full-charge negative electrode sheet thickness - negative electrode sheet thickness after rolling) / (negative electrode sheet thickness after rolling - foil thickness);

[0145] 4C rate charging capacity retention rate detection method: Use the Xinwei charge and discharge test cabinet at 25℃ to charge the battery to 4.2V at a constant current rate of 0.33C, and count the battery charging capacity as C0, and discharge the battery to 2.5V at a constant current rate of 0.33C, and then charge the battery to 4.2V at a constant current rate of 4C, and count the 4C charging capacity as C1, 4C rate charging capacity retention rate = C1 / C0;

[0146] 2.5C / 1C fast charge cycle detection method: Use the Xinwei charge and discharge test cabinet at 25℃ to perform charge and discharge cycles on the battery according to the following steps: 1) Charge to 4.2V with a 2.5C step charge step constant current, and charge to 0.05C with a constant voltage; 2) Let stand for 5 minutes; 3) Discharge to 2.8V with a 1C rate constant current; 4) Let stand for 5 minutes; Perform a cycle test according to steps 1)-4). When the capacity retention rate of the nth cycle reaches 80% or less, n is the number of 2.5C / 1C fast charge cycles, and the capacity retention rate = discharge capacity of the nth cycle / discharge capacity of the 1st cycle.

[0147] Table 2

[0148]

[0149]

[0150] By comparing the data of Examples 1 to 3 and Comparative Examples 1 to 7, it can be proved that: when the silicon-containing layer is in the outermost layer (close to the diaphragm), the rate performance of silicon-carbon / silicon-oxygen is worse than that of graphite, resulting in a low 4C rate charge capacity retention rate and a short 2.5C / 1C cycle life (Comparative Example 4, Comparative Example 5); when the graphite layer is in the outermost layer, the 4C rate charge capacity retention rate of the battery is better, and when the negative electrode is a pure graphite layer (Comparative Example 6), its rate performance is optimal, the fast charge cycle life is the longest, but the energy density is the lowest; when only one silicon-containing layer is provided inside the graphite layer (Comparative Example 1, Comparative Example 2 and Comparative Example 3), due to the respective characteristics of silicon-carbon and silicon-oxygen Point, the battery cannot take into account both high energy density and long fast charging cycle life (the inner layer is only provided with a layer of graphite / new porous silicon-carbon negative electrode. Due to the poor rate performance of the new porous silicon-carbon negative electrode, the fast charging performance is slightly improved; the inner layer is only provided with a layer of graphite / silicon oxide negative electrode. Due to the large expansion of the silicon oxide negative electrode when fully charged, the active material is prone to peeling, resulting in a cycle drop); when the silicon oxide layer is used as the innermost layer (close to the current collector side) and the silicon carbon layer is used as the middle layer (Comparative Example 7), due to the large expansion of the silicon oxide negative electrode when fully charged, the active material is prone to peeling, resulting in cycle deterioration, and the silicon carbon layer has poor rate performance. As an intermediate layer, it cannot help lithium ions migrate to the inner layer quickly.

[0151] It can be seen that the pole piece end needs to be designed more reasonably according to the characteristics of the material itself. The present invention sets the graphite layer as the outermost layer, and utilizes the characteristic of fast diffusion of lithium ions in rate-type graphite to effectively improve the rate performance of the pole piece as a whole, and avoid lithium precipitation on the surface of the negative electrode; the silicon oxygen layer is set as the middle layer, mainly utilizing the characteristic that the silicon oxygen negative electrode has better rate performance than the silicon carbon negative electrode, and providing a buffer layer for slowing down the diffusion rate of lithium ions. In addition, considering that the silicon oxygen negative electrode expands more, placing it in the middle layer can provide an effective buffer space for particle expansion in the longitudinal thickness direction, and reduce the expansion of the pole piece itself; the silicon carbon layer is set as the inner layer, mainly considering the characteristics of high silicon carbon capacity and small expansion, while ensuring the energy density of the battery cell, avoiding the phenomenon of active material shedding caused by large particle expansion, and ensuring the cycle life. The three-layer structure works synergistically to establish a gradient channel (fast-buffer-slow) for lithium ion transmission in the longitudinal direction, so that the battery cell takes into account both energy density and fast charging performance (Examples 1, 2, and 3).

[0152] In addition, from the comparison of Examples 1, 2, and 3, it can be seen that the surface density ratio of the three-layer structure also has a certain influence on the performance. When the surface density ratio of the first silicon-containing layer, the second silicon-containing layer, and the third graphite layer is 50%:30%:20%, the battery cell exhibits the best comprehensive performance.

[0153] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention are within the scope of protection of the pending claims of the present invention.

Claims

1. A silicon-containing negative electrode sheet, characterized in that: It includes a negative electrode current collector and a negative electrode material layer arranged on the surface of the current collector; The negative electrode material layer includes a first silicon-containing layer disposed on the surface of the negative electrode current collector, a second silicon-containing layer disposed on the surface of the first silicon-containing layer, and a third graphite layer disposed on the surface of the second silicon-containing layer; The first silicon-containing layer comprises capacity-type graphite and a novel porous silicon-carbon material, the second silicon-containing layer comprises rate-type graphite and a pre-lithiation silicon-oxygen material, and the third graphite layer comprises rate-type graphite.

2. The silicon-containing negative electrode sheet according to claim 1, characterized in that: In the first silicon-containing layer, the capacity of the capacity-type graphite is 355-360 mAh / g and the compaction is 1.6-1.7 g / cm 3 ; And / or, the capacity of the novel porous silicon-carbon material at 5mV-0.8V is 1600-1750mAh / g.

3. The silicon-containing negative electrode sheet according to claim 1, characterized in that: The rate-type graphite in the second silicon-containing layer and the third graphite layer has a capacity of 345-355 mAh / g and a compaction of 1.5-1.65 g / cm 3 ; Preferably, the rate of the rate-type graphite in the second silicon-containing layer is 1-1.5C lower than the rate of the rate-type graphite in the third graphite layer; And / or, the capacity of the pre-lithiated silicon-oxygen material in the second silicon-containing layer at 5mV-0.8V is 1200-1350mAh / g.

4. The silicon-containing negative electrode sheet according to claim 1, characterized in that: The raw materials used to form the first silicon-containing layer include capacitive graphite, a novel porous silicon-carbon material, a conductive agent and a binder. Taking the total mass of the raw materials used to form the first silicon-containing layer as 100%, the mass fraction ratio of the capacitive graphite, the novel porous silicon-carbon material, the conductive agent and the binder is (83.5%-88.4%): (7.6%-11.5%): (0.5%-1%): (3.5%-4%); And / or, the raw materials used to form the second silicon-containing layer include rate-type graphite, pre-lithiation silicon-oxygen material, conductive agent and binder, and the mass fraction ratio of the rate-type graphite, pre-lithiation silicon-oxygen material, conductive agent and binder is (78.2%-88.5%): (7.5%-16.3%): (1%-1.5%): (3%-4%), taking the total mass of the raw materials used to form the second silicon-containing layer as 100%. And / or, the raw materials used to form the third graphite layer include rate-type graphite, a conductive agent and a binder. Taking the total mass of the raw materials used to form the third graphite layer as 100%, the mass ratio of the rate-type graphite, the conductive agent and the binder is (95.5%-96.5%): (1%-1.5%): (2.5%-3%).

5. The silicon-containing negative electrode sheet according to claim 4, characterized in that: The conductive agent in the first silicon-containing layer, the second silicon-containing layer and the third graphite layer comprises conductive carbon black and / or carbon nanotubes; and / or, the binder in the first silicon-containing layer, the second silicon-containing layer and the third graphite layer comprises at least one of styrene-butadiene rubber, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polyacrylic acid or lithium polyacrylate; And / or, the mass fraction ratio of the binder in the second silicon-containing layer is less than or equal to the mass fraction ratio of the binder in the first silicon-containing layer.

6. The silicon-containing negative electrode sheet according to claim 5, characterized in that: The conductive agents in the first silicon-containing layer and the second silicon-containing layer include conductive carbon black and single-walled carbon nanotubes; And / or, the binder in the first silicon-containing layer and the second silicon-containing layer includes styrene-butadiene rubber and lithium polyacrylate.

7. The silicon-containing negative electrode sheet according to claim 4, characterized in that: The composite gram capacity of the negative electrode of the second silicon-containing layer is less than or equal to the composite gram capacity of the negative electrode of the first silicon-containing layer; And / or, the surface density of the first silicon-containing layer accounts for 30%-60% of the surface density of the negative electrode material layer, the surface density of the second silicon-containing layer accounts for 30%-50% of the surface density of the negative electrode material layer, and the surface density of the third graphite layer accounts for 10%-20% of the surface density of the negative electrode material layer.

8. The method for preparing a silicon-containing negative electrode sheet according to any one of claims 1 to 7, characterized in that: The following steps are involved: (a) coating a raw material for forming a first silicon-containing layer and a raw material for forming a second silicon-containing layer on at least one side of a current collector by a double-layer coating technique, and then drying to form a first silicon-containing layer and a second silicon-containing layer, respectively, and then rolling the first silicon-containing layer and the second silicon-containing layer; (b) coating a raw material for forming a third graphite layer on the surface of the second silicon-containing layer, and then drying to form the third graphite layer, and then rolling the entire electrode sheet to obtain a silicon-containing negative electrode sheet.

9. The method for preparing a silicon-containing negative electrode sheet according to claim 8, characterized in that: In step (a), the rolling includes a first rolling and a second rolling, and the first rolling compaction is 1.3-1.4 g / cm 3 The second roller compaction is 1.6-1.65g / cm 3 ; And / or, in step (b), the roller compaction is 1.55-1.6 g / cm 3 .

10. A lithium ion battery, characterized in that: The invention relates to a silicon-containing negative electrode sheet comprising the silicon-containing negative electrode sheet as described in any one of claims 1 to 7 and the silicon-containing negative electrode sheet prepared by the preparation method as described in claim 8 or 9.

Citation Information

Patent Citations

  • Negative pole piece of lithium ion battery, preparation method of negative pole piece and lithium ion battery

    CN116314605A

  • Silicon-based negative pole piece, preparation method thereof and lithium ion battery

    CN116387448A

  • Negative plate and lithium ion secondary battery

    CN118588863A

  • Negative electrode and secondary battery

    CN118661281A

  • Lithium Secondary Battery

    US20240128491A1

Cited By

  • Electrode plate containing silicon negative electrode, battery and preparation method of electrode plate

    CN120600764A